Desain Program Pelaporan yang Optimal: Analisis Kualitatif Terhadap Efek Pemberian Insentif dan Dinamika Keterlibatan Pelapor - Eka Wahyu Kasih; Ngadi Permana; A. Sigit Pramono Hadi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to analyze the optimal design of whistleblowing programs, focusing on the effects of incentives and the dynamics of whistleblower engagement. Through a qualitative literature review, the research explores the impact of financial incentives on the effectiveness of whistleblowing programs and how factors such as organizational culture and management support influence whistleblowers' decisions. The findings show that while financial incentives are effective in encouraging reporting, excessive incentives can reduce the quality of the information provided. On the other hand, factors such as anonymity and protections for whistleblowers significantly increase their engagement. This study highlights the importance of a holistic approach that combines financial and non-financial incentives with strong protections for whistleblowers to ensure program effectiveness. Furthermore, policy implications suggest the need for continuous evaluation of whistleblowing programs to ensure they remain relevant and effective in detecting violations across different sectors. Although this study provides valuable insights, several limitations, including its focus on literature sourced from the United States and the absence of empirical data, affect the generalization of the findings. Therefore, further research is necessary to test these findings in various organizational contexts and environments.